Proceedings of the 20th Annual International Conference on Supercomputing 2006
DOI: 10.1145/1183401.1183428
|View full text |Cite
|
Sign up to set email alerts
|

Design space exploration for multicore architectures

Abstract: Multicore architectures are ruling the recent microprocessor design trend. This is due to different reasons: better performance, threadlevel parallelism bounds in modern applications, ILP diminishing returns, better thermal/power scaling (many small cores dissipate less than a large and complex one); and, ease and reuse of design.This paper presents a thorough evaluation of multicore architectures. The architecture we target is composed of a configurable number of cores, a memory hierarchy consisting of privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 23 publications
1
38
0
Order By: Relevance
“…As expected, some differences were obtained mainly due to the different architecture organization modeled in both simulators as well as the different instruction set architectures. Moreover, the overall distribution of the power consumption among the main hardware structures presented in a tiled chip multiprocessor agree with the results reported by different researchers [17,19,25].…”
Section: Validation Of the Power Model Of Sim-powercmpsupporting
confidence: 89%
See 2 more Smart Citations
“…As expected, some differences were obtained mainly due to the different architecture organization modeled in both simulators as well as the different instruction set architectures. Moreover, the overall distribution of the power consumption among the main hardware structures presented in a tiled chip multiprocessor agree with the results reported by different researchers [17,19,25].…”
Section: Validation Of the Power Model Of Sim-powercmpsupporting
confidence: 89%
“…As expected, it can be observed that most of the power is dissipated in the processor cores of the CMP. In particular, the ALU reveals as one of the most consuming structures of the CMP, as reported in [17]. Regarding the caches (private L1 caches and the shared multibanked L2 cache), we can see that their fraction of the total power is quite significant.…”
Section: Experimental Frameworkmentioning
confidence: 69%
See 1 more Smart Citation
“…Functional units can also be resized to accommodate a lower power density [23], but with a reduction of the clock frequency and negative impact on processor performance. Floorplan can also be conveniently designed to accommodate thermal hot-spots as done in [19].…”
Section: A Design-time Thermal Optimizationmentioning
confidence: 99%
“…Efforts in high-k materials have reduced the gate-oxide leakage; nevertheless lower voltages increase dramatically subthreshold leakage. Both academic and industrial studies show that a large part of the power consumption of a state-of-the-art processor is due to the static component [1]- [3]. According to the ITRS [4], efficiently managing low-leakage devices and operation modes is a key challenge for next generation systems.…”
Section: Introductionmentioning
confidence: 99%